How social practices inform the future as method: Describing personas in an energy transition while engaging with teleoaffectivities. (April 2023) - Sahakian, Marlyne; Moynat, Orlane; Senn, Wladyslaw; Moreau, Vincent
Abstract: In the sociology of expectations, the future is seen as performative in the present: how energy futures are imagined has consequences for how the energy transition might be enacted today. This contribution discusses the conceptual and methodological work undertaken to develop personas from the future, on their way to the policy aim of so-called 'net zero' carbon emissions by 2050 in Switzerland. Social practice theoretical reflections contribute in three ways: conceptually, in recognizing the future orientation of teleoaffectivities; methodologically, for describing personas engaged in future practices; and towards reflexivity, in how imagining futures might affect social practices today. Moving from policy-relevant to practice-oriented energy scenarios is described as an iterative process that involves different stages of consultation. The process is not without tensions, calling into question how change is understood, and revealing the strengths and limits of trans- and inter-disciplinary approaches. A social practice-based approach provided a method for rich descriptions of futures, moving beyond changes to technologies that are ubiquitous in energy scenarios, to also include changes in meanings and competencies, as well as broader socio-cultural dynamics. The treatment of the social energy futures in cartoon form and through storytelling also allowed for a more compelling and engaging representation of the future, which might affect teleoaffectivities in the present. Highlights: Policy-oriented energy scenarios are limited tools for citizens. Practice-oriented scenarios, through personas, are more relatable. Developing futures requires an open, iterative process of co-knowledge production. Energy saving potentials in the future depend on income quintile and are unequal. The future as method has the potential to be performative in the present.